2014
DOI: 10.1038/nbt.2968
|View full text |Cite
|
Sign up to set email alerts
|

Self-hydrolyzing maleimides improve the stability and pharmacological properties of antibody-drug conjugates

Abstract: Many antibody-drug conjugates (ADCs) are unstable in vivo because they are formed from maleimide-containing components conjugated to reactive thiols. These thiosuccinimide linkages undergo two competing reactions in plasma: elimination of the maleimide through a retro-Michael reaction, which results in loss of drug-linker from the ADC, and hydrolysis of the thiosuccinimide ring, which results in a derivative that is resistant to the elimination reaction. In an effort to create linker technologies with improved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
338
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 373 publications
(365 citation statements)
references
References 28 publications
13
338
0
2
Order By: Relevance
“…It has previously been reported that replacement of the MC stretcher with mDPR has no effect on in vitro ADC potency and activity, but that the improved stability may lead to increased in vivo potency in a model-dependent manner (15). On the basis of these results, the impact of mDPR inclusion on intratumoral drug delivery was assessed.…”
Section: Mdpr Inclusion Increases Mmae Delivery In Vivo and Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…It has previously been reported that replacement of the MC stretcher with mDPR has no effect on in vitro ADC potency and activity, but that the improved stability may lead to increased in vivo potency in a model-dependent manner (15). On the basis of these results, the impact of mDPR inclusion on intratumoral drug delivery was assessed.…”
Section: Mdpr Inclusion Increases Mmae Delivery In Vivo and Stabilitymentioning
confidence: 99%
“…The self-stabilizing maleimide (mDPR; Fig. 1) was developed to undergo rapid postconjugation thiosuccinimide hydrolysis, to provide circulation-stable ADCs with a wider therapeutic window (15).…”
Section: Introductionmentioning
confidence: 99%
“…Using this approach, an ADC is produced that is homogeneous and bears an average of 16 total drugs, split evenly between the two drug linkers. The carrier utilizes two recent advancements for the construction of ADCs with improved pharmacological activity: a self‐stabilizing maleimide (mDPR) to minimize drug‐linker deconjugation in vivo,2a and a PEG 24 stretcher to enable high drug loading without concomitant hydrophobicity‐induced ADC aggregation 6…”
mentioning
confidence: 99%
“…B) A multiplexing drug carrier 4 bearing Cys(SiPr) and Cys(Acm) groups that can be unmasked using orthogonal conditions. The carrier also contains a PEG 24 group to mask drug‐linker hydrophicity6 and a self‐stabilizing maleimide (mDPR)2a for antibody attachment. C) Homogeneous dual‐drug ADCs prepared using 4 bear 16 total drugs, split evenly (8+8) between the two component drugs.…”
mentioning
confidence: 99%
“…This technology, when applied to trastuzumab emtansine, yields a defined DAR of 2, and the authors believe that the antitumor activity and stability is increased compared to drug conjugates produced with the THIOMAB method. A possible explanation might be that a retro-Michael addition, leading to the transfer of drugs conjugated to cysteines to free thiols in blood serum components, may have partially inactivated the ADC [76][77][78] . However, the authors do not provide convincing data showing that their own preparation of the THIOMAB antibody had a DAR of 2, as it was published by Junutula et al 50 .…”
Section: Click Chemistries For Bioconjugationmentioning
confidence: 99%